The 30-day readmission of same-day discharge following pulmonary vein isolation for atrial fibrillation: a propensity score-matched analysis from National Readmission Database. (14th October 2021) - Sahashi, Y; Kuno, T; Malik, A.H; Briasoulis, A
Abstract: Introduction: The complication rate following pulmonary vein isolation (PVI) for atrial fibrillation (AF) has improved in recent decades with the increasing number of PVI worldwide. The effectiveness and safety of same-day discharge for PVI has not been elucidated well using a large nationwide database. Purpose: The aim of our study was to evaluate the readmission rates within 30-days among patients receiving PVI for AF with the same-day discharge compared with the usual overnight observation protocol. Methods: We performed a retrospective cohort study using the US Nationwide Readmission Database. Patients were divided into the two groups: the same-day discharge group and the overnight observation group (those who stayed at least one night following PVI). The primary outcome was an all-cause 30-day readmission rate following discharge in patients receiving PVI and a secondary outcome of total healthcare cost. A 1:3 propensity score matching was used to compare the safety within both protocols. Patients with peri-procedural complications such as pericardial, vascular, bleeding requiring transfusion, were excluded from the analysis. Result: Among 30, 776 patients (mean 67.2±11.4 years, 18, 004 male (58.5%)) who received PVI from 2016 through 2018, 440 (1.42%) patients were discharged the same-day following PVI (same-day discharge group), and the remaining 30, 336 patients stayed at least one night in the hospital (the overnight observation group). A propensity score analysis generated 1, 751 matched pairs (440 in the same-day discharge group; 1311 in the observation overnight group). The 30-day readmission following discharge was not significantly higher in the same-day discharge group, compared to the overnight observation group (same-day discharge vs. overnight observation group: 12.7% vs. 9.7%, p=0.23; odds ratio [OR]:1.39, 95%confidence interval [CI]: 0.87–2.22) (Figure). Healthcare cost was significantly higher in the overnight observational group. ($25, 237±14, 036 vs. $30, 749±16, 383; p<0.01). Conclusion: In this large nationwide study using a propensity score matching analysis, there was no significant difference in 30-day readmission rates following the same-day discharge in patients receiving PVI for AF compared with the overnight observation protocol. Funding Acknowledgement: Type of funding sources: None.